Pengaruh Persepsi Kemudahan Penggunaan, Literasi Keuangan, Efektivitas, Dan Kemampuan Finansial Terhadap Minat Penggunaan Qris Dalam Transaksi Pembayaran (Studi Kasus Mahasiswa S1 Universitas Amikom Yogyakarta) - Poncowati, Neny Rossita; Sutarni, Sutarni (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
This research aims to test empirically the perceived ease of use has a positive and significant effect on interest in using QRIS in payment transactions among undergraduate students at Amikom University, Yogyakarta, financial literacy has a positive and significant effect on interest in using QRIS in payment transactions among undergraduate students. Amikom University Yogyakarta, effectiveness has a positive and significant effect on interest in using QRIS in payment transactions among undergraduate students at Amikom University Yogyakarta, financial capability has a positive and significant effect on interest in using QRIS in payment transactions among undergraduate students at Amikom University Yogyakarta, perception ease of use, financial literacy, effectiveness, and financial capability simultaneously have a significant influence on interest in using QRIS in payment transactions among undergraduate students at Amikom University, Yogyakarta. This research is quantitative research using a quantitative approach method. The population in this study were undergraduate students at Amikom University Yogyakarta and used primary data as a data collection method by distributing questionnaires and getting 100 respondents using purposive sampling techniques. The analysis technique used in this research is multiple linear regression analysis with the help of the Statistical Package Social Science (SPSS) vs 29 program. The results of this research show that perception of ease of use has a positive and significant effect on interest in using QRIS in payment transactions, financial literacy has a positive and insignificant effect on interest in using QRIS in payment transactions, effectiveness has a positive and insignificant effect on interest in using QRIS in payment transactions, financial ability has a positive and significant effect on interest in using QRIS in payment transactions, perception of ease of use, financial literacy, effectiveness and financial capability simultaneously have a significant influence on interest in using QRIS in payment transactions.